(untitled) (Raparin Journal of Humanities (RJH), 2024)
Olives have been of great importance in ancient civilizations, since the beginning of life, scientists have different opinions on the origin of this tree, some Palestine and Syria, some Greeks and some Cyprus and the Aegean Sea region In the sources and languages of the world, the name is mentioned in different ways, because Movi was not very experienced at that time, he initially regarded it as an ordinary tree and treated its branches and fruits In many religions and throughout different times, its oil has been the purest and best way to show their relationship with God, so in the time of kings and princes Prominent figures, aristocrats, heroes, athletes and clerics, East and West, used perfumed oil to show their holiness and high social status. It was one of the pillars of Egyptian and Greek civilization, especially in ancient Greece It was a food that they called liquid gold, but because of its effects on religious thought and thought after death, the title of the study (The importance of olives and their oil in ancient Egyptian and Greek civilizations), which consists of three main topics. The first topic: The name of the olive, its history of development, its distribution areas and its causes and motives. The second topic : its religious position in both civilizations. The third topic: the importance of the use of olives and their oil in different fields of both civilizations